MENINGKATKAN KEMAMPUAN MOTORIK KASAR ANAK USIA 4-5 TAHUN MELALUI PERMAINAN SIRKUIT LOKOMOTOR DI TKQ AL-MU’MIN ANTAPANI BANDUNG - Tanti Tri Aristianti; Esty Faatinisa; Yulia Nur Annisa (LPPM Universitas Bina Bangsa, 2022)
This class action research aims to improve the gross motor skills of children aged 4-5 years through locomotor circuit games at TKQ Al-Mu'min Antapani Bandung. This study is a class-action study, the model used is the Kemmis and Taggart model, which consists of 2 cycles. The study subjects numbered 18 children consisting of 9 boys and 9 girls. Data collection uses observation techniques(cheklish). Data analysis techniques use qualitative descriptive techniques. The increase in gross motor ability is said to be successful if the presentation of gross motor skills of children reaches 80% (criteria for being able to perform locomotor, non-locomotor, and manipulative movements). The results of this study prove that locomotor circuit games can improve the gross motor skills of children aged 4-5 years TKQ Al-Mu'min. This is evidenced by an increase in the gross motor skills of children, in cycle I for locomotor motion by 45%, non-locomotor motion by 39%, and manipulative motion by 45%. In cycle II it increases for locomotor motion by 83%, non-locomotor motion by 83%, and manipulative motion by 88%. Based on the results of the above analysis on cycle I and cycle II, the author can conclude that locomotor circuit games can improve gross motor skills of children aged 4-5 years at TKQ Al-Mu'min Antapani Bandung